Fit Sigma : a lean approach to building sustainable quality beyond Six Sigma - Basu, Ron (Wiley, 2011)
"Developed through the study of Six Sigma, Fit Sigma[trademark symbol] integrates the 'hard' Six Sigma approach with Lean enterprise philosophy. It has three elements; fitness for purpose, fitness for improvement and integration, and fitness for sustainability. This book shows how to add value to both large and small organisations through improved use of resources, and through the provision of improved customer satisfaction by implementing Fit Sigma[trademark symbol]. The book gives comprehensive insight into tools and techniques of continuous improvement in one package, providing a step-by-step guide to applying Fit Sigma[trademark symbol] tools to the improvement process - each chapter contains a practical implementation guide and illustrative examples and case studies. It shows that a holistic approach of operational excellence driven by a data driven methodology can be applied equally to manufacturing, service or public sectors. The business environment and global market dynamics are evolving and new challenges include climate change, green supply chain, emerging markets and a growing service sector. The methodology and thinking in Six Sigma are also changing. Fit Sigma[trademark symbol]: A Lean Green Approach to building Quality beyond Six Sigma takes into account the changes in these tools, challenges and opportunities. The book covers key developing areas such as the Sustainability and the Environment, Service operations, Events management, Project management, Small and medium enterprises, Non profit organizations, Supply chain management, and Emerging markets."--Resumé vydavatele